Remediation of Methylene blue and Rhodamine B using various adsorbents-A Review - Panjwani, Bhawna; Verma, Kiran (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The remediation of methylene blue dye and Rhodamine B from waste water using different adsorbents is being studied by various researchers. In recent years, the uses of various naturally available adsorbents have been widely used as a replacement for the current costly methods of treatment of waste water. In this review, a wide range of adsorbents which have been studied have been listed and there efficiency upon various parameters have been mentioned. Different kinds of adsorbents such as activated carbons from different sources, biological wastes and modern modified adsorbents have been enlisted. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>